Emission Rates of Volatile Organic Compounds Released from Newly Produced Household Furniture Products Using a Large-Scale Chamber Testing Method - Duy Xuan Ho; Ki-Hyun Kim; Jong Ryeul Sohn; Youn Hee Oh; Ji-Won Ahn (The Scientific World Journal)
The emission rates of volatile organic compounds (VOCs) were measured to investigate the emission characteristics of five types of common furniture products using a 5 m3 size chamber at 25°C and 50% humidity. The results indicated that toluene and α-pinene are the most dominant components. The emission rates of individual components decreased constantly through time, approaching the equilibrium emission level. The relative ordering of their emission rates, if assessed in terms of total VOC (TVOC), can be arranged as follows: dining table > sofa > desk chair > bedside table > cabinet. If the emission rates of VOCs are examined between different chemical groups, they can also be arranged in the following order: aromatic (AR) > terpenes (TER) > carbonyl (CBN) > others > paraffin (PR) > olefin (HOL) > halogenated paraffin (HPR). In addition, if emission strengths are compared between coated and uncoated furniture, there is no significant difference in terms of emission magnitude. Our results indicate that the emission characteristics of VOC are greatly distinguished between different furniture products in terms of relative dominance between different chemicals.